RNA m 6 A modification, signals for degradation or stabilisation? - Wei, G (Portland Press, 2024)
The RNA modification N6-methyladenosine (m6A) is conserved across eukaryotes, and profoundly influences RNA metabolism, including regulating RNA stability. METTL3 and METTL14, together with several accessory components, form a ‘writer’ complex catalysing m6A modification. Conversely, FTO and ALKBH5 function as demethylases, rendering m6A dynamic. Key to understanding the functional significance of m6A is its ‘reader' proteins, exemplified by YTH-domain-containing proteins (YTHDFs) canonical reader and insulin-like growth factor 2 mRNA-binding proteins (IGF2BPs) non-canonical reader. These proteins play a crucial role in determining RNA stability: YTHDFs mainly promote mRNA degradation through different cytoplasmic pathways, whereas IGF2BPs function to maintain mRNA stability. Additionally, YTHDC1 functions within the nucleus to degrade or protect certain m6A-containing RNAs, and other non-canonical readers also contribute to RNA stability regulation. Notably, m6A regulates retrotransposon LINE1 RNA stability and/or transcription via multiple mechanisms. However, conflicting observations underscore the complexities underlying m6A's regulation of RNA stability depending upon the RNA sequence/structure context, developmental stage, and/or cellular environment. Understanding the interplay between m6A and other RNA regulatory elements is pivotal in deciphering the multifaceted roles m6A plays in RNA stability regulation and broader cellular biology.